Contextualising the Conflicts of American Economic Beliefs in Kurt Vonnegut’s Jailbird - T. Akshayaa; Dr. R. Sankari (Revista Electronica de Veterinaria, 2024)
This paper aims to explore how, in Jailbird (1979), Kurt Vonnegut relentlessly challenges economic misconceptions in America that stem from ideas of egalitarianism, meritocracy, and equal opportunity. Additionally, it assesses how he creatively links the origins of economic disparity to American history rather than viewing it as a brand-new problem. In Jailbird, Walter F. Starbucks’ life is examined, with particular attention paid to how, two days after his release, this alleged participant in the Watergate conspiracy rises to become the vice president of RAMJAC, the biggest corporation in the world. The novel is a satirical critique of American society’s impersonality, corruption, and loneliness. The two main emblems of the political and economic ills are Watergate and RAMJAC. With the support of his surrogate parents, Sacco and Vanzetti, as well as the three strong female mentors - his wife Ruth, Sarah Wyatt, and Mary Looney - Starbuck, who was a passive and innocuous accomplice in Nixon’s Watergate scandal, shambles his way through a few tests towards a sort of moral heroism in defeat. Vonnegut portrays crony capitalism and money as dehumanising factors in American culture.